2011
DOI: 10.3892/mmr.2011.701
|View full text |Cite
|
Sign up to set email alerts
|

Matrine inhibits proliferation and induces apoptosis of the androgen‑independent prostate cancer cell line PC-3

Abstract: Abstract. Current strategies to treat androgen-independent prostate cancer are associated with a number of challenges and are not yet curative. Matrine is a naturally occurring alkaloid extracted from the Chinese herb Sophora flavescens. Matrine has shown anti-proliferative properties in a number of types of cancer, including breast, gastric, lung and pancreatic tumors. Matrine was also found to promote apoptosis and inhibit invasion of cancer cells. We evaluated the antitumor effects of matrine on androgen-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…MMPs, especially MMP-2 and MMP-9, are believed to be potent in degrading ECM [7,17,21]. Matrine has been proved to be able to reduce the expression of MMPs in many cancers [22,23]. In the study, we found that matrine reduced the expression and activity of MMP-2 and MMP-9 in CRC cells.…”
Section: Discussionsupporting
confidence: 54%
“…MMPs, especially MMP-2 and MMP-9, are believed to be potent in degrading ECM [7,17,21]. Matrine has been proved to be able to reduce the expression of MMPs in many cancers [22,23]. In the study, we found that matrine reduced the expression and activity of MMP-2 and MMP-9 in CRC cells.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly we found water extract of HWD can arrest the HepG2 cells in G0/G1 phase via downregulating the mRNA and protein levels of CDK2, CDK4 and E2F (10). Matrine, a component rich in SF, inhibited cell proliferation through arresting cells in G0/G1 phase in gallbladder cancer cells (31), prostate cancer cells (32) and hepatoma cells (33). Qin et al and Zhao et al reported that matrine downregulated the expression of cyclin D1 to inhibit the growth of retinoblastoma cells (34,35).…”
Section: Discussionsupporting
confidence: 51%
“…As a main alkaloid from Sophora flavescens Ait, matrine (C 15 H 24 N 2 O) also exhibits a variety of biological activities such as anti-inflammation, antivirus, anti-fibrosis, anti-arrhythmia and immunosuppression [7]. Moreover, recent studies have reported that matrine also possesses antitumor activities by inhibiting proliferation and inducing apoptosis against a wide range of cancers, including lung cancer, gastric cancer, breast cancer and so on [8,9,10,11,12,13,14]. Accordingly, our previous study demonstrated that matrine significantly inhibited growth of human nasopharyngeal carcinoma cells in a dose- and time-dependent manner.…”
Section: Introductionmentioning
confidence: 99%